Testing antimicrobial susceptibilities of adherent bacteria by a method that incorporates guidelines of the National Committee for Clinical Laboratory Standards. - Domingue, G (1994)
Membrane filters (0.22-microns pore size) were colonized with 10(4) CFU of logarithmic-phase bacteria per filter under laminar flow conditions in a Modified Robbins Device. Colonized filters were then placed upon agar dilution plates for MIC determinations. Subsequently, filters were transferred to control plates and incubated to obtain MBCs.